2000
DOI: 10.1046/j.1365-3040.2000.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence implicating a novel thiol methyltransferase in the detoxification of glucosinolate hydrolysis products in Brassica oleracea L.

Abstract: The physiological relevance of a novel thiol methyltransferase from cabbage, and its possible role in sulphur metabolism have been investigated. The enzyme was absent from the chloroplast, the site of sulphate reduction, and was localized in the cytosol. Potential substrates were initially screened on the basis of their ability to inhibit the methylation of iodide, a previously known substrate for the enzyme. Thiocyanate, 4,4¢-thiobisbenzenethiol, thiophenol, and thiosalicylic acid were identified as possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 44 publications
0
29
1
Order By: Relevance
“…It thus appears that mono-methylation by MT-II is a much faster reaction compared to bis-thiomethylation and that this subsequent activity results in a progressive incorporation of methyl groups [11]. In plants, the biological function of thiol methyltransferases (TMTs) has been associated with the detoxification of xenobiotics, for example: reactive thiols produced during the degradation of glucosinolate in cabbage, like thiocyanate and thiosalicylic acid, are detoxified by a TMT that thiomethylates them into non-reactive derivatives [42]. The same role was observed in Phycomitrella patens, whereby PpSABATH1 was responsible for the detoxification of thiobenzoic acid [43].…”
Section: Discussionmentioning
confidence: 99%
“…It thus appears that mono-methylation by MT-II is a much faster reaction compared to bis-thiomethylation and that this subsequent activity results in a progressive incorporation of methyl groups [11]. In plants, the biological function of thiol methyltransferases (TMTs) has been associated with the detoxification of xenobiotics, for example: reactive thiols produced during the degradation of glucosinolate in cabbage, like thiocyanate and thiosalicylic acid, are detoxified by a TMT that thiomethylates them into non-reactive derivatives [42]. The same role was observed in Phycomitrella patens, whereby PpSABATH1 was responsible for the detoxification of thiobenzoic acid [43].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that methyl chloride transferase (MCT) from Batis maritima (Wuosmaa and Hager 1990;Ni and Hager 1998) and thiol methyltransferases (TMT) from Brassica oleracea (Attieh et al 2000a;Attieh et al 2000b;Attieh et al 2002) possess S-adenosyl-L-methionine (SAM)-dependent methyltransferase activities and could synthesize methyl halide in vitro (Attieh et al 2000a;Wousmaa and Hager 1990). The hypotheses concerning the physiological meaning of these enzymes include their involvement in salt tolerance (Ni and Hager 1999) or in metabolizing glucosinolate hydrolysis products such as thiols and thiocyanate (Attieh et al 2000a).…”
mentioning
confidence: 99%
“…The hypotheses concerning the physiological meaning of these enzymes include their involvement in salt tolerance (Ni and Hager 1999) or in metabolizing glucosinolate hydrolysis products such as thiols and thiocyanate (Attieh et al 2000a). The AtHOL1 gene was isolated from Arabidopsis as the MCT homolog, and the T-DNA insertion mutant analyses revealed that AtHOL1 was involved in the synthesis of methyl halides including methyl chloride, methyl bromide, and methyl iodide (Rhew et al 2003).…”
mentioning
confidence: 99%
“…Homologues of this enzyme have been found in several organisms, such as higher plants (Attieh et al 2000;Itoh et al 2009), algae (Itoh et al 1997), fungi, and soil bacteria (Amachi et al 2001) In this study, various marine phytoplankton were cultivated in order to clarify the molecular formation mechanism of methyl halides and to establish a correlation between intracellular halide ion methyl transferase/halide ion thiol methyl transferase (HTM/HTMT) activity and CH 3 X emission. The enzyme genes were isolated from marine phytoplankton, verified, expressed in E. coli, and characterized in detail.…”
Section: Elucidation Of the Mechanism Of Methylmentioning
confidence: 99%